Stimulation of soluble guanylate cyclase by vericiguat reduces skeletal muscle atrophy of mice following chemotherapy - Hu, Bo-ang; Li, Yu-lin; Han, Hai-tao; Lu, Bin; Jia, Xu; Han, Lu; Ma, Wei-xuan; Zhu, Ping; Wang, Zhi-hao; Zhang, Wei; Zhong, Ming; Zhang, Lei (Frontiers in Pharmacology, 2023)
Background The chemotherapeutic doxorubicin (DOX) promotes severe skeletal muscle atrophy, which induces skeletal muscle weakness and fatigue. Soluble guanylate cyclase (sGC) contributes to a variety of pathophysiological processes, but whether it is involved in DOX-induced skeletal muscle atrophy is unclear. The present study aimed to stimulate sGC by vericiguat, a new oral sGC stimulator, to test its role in this process. Methods Mice were randomly divided into four groups: control group, vericiguat group, DOX group, and DOX+vericiguat group. Exercise capacity was evaluated before the mice were sacrificed. Skeletal muscle atrophy was assessed by histopathological and molecular biological methods. Protein synthesis and degradation were monitored in mice and C2C12 cells. Results In this study, a significant decrease in exercise capacity and cross-sectional area (CSA) of skeletal muscle fibers was found in mice following DOX treatment. Furthermore, DOX decreased sGC activity in mice and C2C12 cells, and a positive correlation was found between sGC activity and CSA of skeletal muscle fibers in skeletal muscle. DOX treatment also impaired protein synthesis, shown by puromycin detection, and activated ubiquitin‐proteasome pathway. Following sGC stimulation, the CSA of muscle fibers was elevated, and exercise capacity was enhanced. Stimulation of sGC also increased protein synthesis and decreased ubiquitin‐proteasome pathway. In terms of the underlying mechanisms, AKT/mTOR and FoxO1 pathways were impaired following DOX treatment, and stimulation of sGC restored the blunted pathways. Conclusions These results unravel sGC stimulation can improve skeletal muscle atrophy and increase the exercise capacity of mice in response to DOX treatment by enhancing protein synthesis and inhibiting protein degradation. Stimulation of sGC may be a potential treatment of DOX-induced skeletal muscle dysfunction.